2009
DOI: 10.1021/am800122n
|View full text |Cite
|
Sign up to set email alerts
|

Blue to True-Blue Phosphorescent IrIII Complexes Bearing a Nonconjugated Ancillary Phosphine Chelate: Strategic Synthesis, Photophysics, and Device Integration

Abstract: We report the design and synthesis of Ir(III) complexes functionalized with substituted pyridyl cyclometalate or azolate chromophores, plus one newly designed nonconjugated phosphine chelate, which not only greatly restricts its participation in the lowest-lying electronic transition but also enhances the coordination strength. These two key factors lead to fine-tuning of the phosphorescence chromaticity toward authentic blue and simultaneously suppress, in part, the nonradiative deactivation. This conceptual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 79 publications
1
29
0
Order By: Relevance
“…The synthetic procedure is shown in Scheme 1. The properties of the chloride salts are nearly consistent with those of the PF 6 -salts discussed herein.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The synthetic procedure is shown in Scheme 1. The properties of the chloride salts are nearly consistent with those of the PF 6 -salts discussed herein.…”
Section: Resultssupporting
confidence: 74%
“…, reflecting that the π-accepting character of the phosphine group increased the associated MLCT energy levels, resulting in a blue-shift emission. 6 The substituents in the main ligand showed a hypsochromic shift on the order of ppy → dfppy → dfmppy, and revealed that difluorination on the 2,4-positions of the phenyl ring led to a significant blue-shift, whereas methylation on the pyridine group caused a small blue-shift of the emission maximum. 22 The emission peaks were next examined in a variety of solvents, but little solvatochromism was observed as shown in Table 2.…”
mentioning
confidence: 99%
“…In fact, there are also several of strategies to tune the emission color or efficiency of the Ir(III) complexes, such as designing new cyclometalating ligands, ancillary ligands, or attaching different substituents [24][25][26][27]. It is noted that electron deficient and/or higher field strength L\widehatX ancillaries, such as pyridylazolate and imidodiphosphinate, and phosphorus-containing chelates, such as benzyl phosphine and phosphine substituted pyrazole, are very suitable for the construction of blue-or even bluish-green-emitting Ir(III) metal phosphors [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as for iridium-containing emitters, the internal quantum efficiency of about 100% is higher than that based on fluorescence [14], because they are capable of harvesting both singlet and triplet excitons, while fluorescent emitters are limited to singlet excitons [15,16]. It is well known that phosphorescent iridium(III) complexes can realise emission in the full visible spectra by modifying the ligand structure and/or incorporation of ancillary ligands [17,18]. The introduction of electron-donating or electron-withdrawing substituents to the coordinated ligands is the most common approach to tune the emission energy [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%